PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, PENGALAMAN AUDITOR DAN INDEPENDENSI TERHADAP AUDIT JUDGMENT (Studi Empiris Pada Kantor Akuntan Publik Pekanbaru, Padang, Batam) - Apandi1 Irpan; Hardi Hardi; Meilda Meilda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of obedience pressure, task complexity,auditor experience and independency on auditor judgement. This study uses primary data collected by distributing questionnaires to the auditor who worked in the Public Accountant Office located in Pekanbaru, Padang and Batam. From 80 questionnaires distributed to twenty Public Accountant Office, total questionnairs returned and can be processed is 68 questionnaires. After validitiy and reliability test done, data is analyzed using multiple linear regression method with IBM SPSS (Statistical Product and Service Solution) statistical tools 17. The research results show obedience pressure have positive impact on the auditor judgement, auditor experience have positive impact on the auditor judgement, independency have positive impact on the auditor judgement and while the task complexity causes negative effect on auditor judgement.Keywords: Obedience Pressure, Task Complexity, Auditor Experience, Independency, Audit Judgment